2008
DOI: 10.1002/glia.20758
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of P2X7 receptor expression in rat oligodendrocyte precursor cells after hypoxia ischemia

Abstract: Oligodendrocyte precursor cells (OPCs) are the predominant oligodendrocyte-lineage stage in the cerebral hemispheres of neonatal rat. Prior studies have shown that OPCs are highly vulnerable to hypoxic-ischemic injury, yet the mechanisms are not well understood. P2X 7 receptor (P2X 7 R) is an ATP-gated ion channel that has unusual properties and plays very complex roles in a variety of neuropathologic conditions. However, little is known about the involvement of P2X 7 R in OPCs development and injury. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 73 publications
1
52
0
1
Order By: Relevance
“…However, inconsistent with most reports that P2X 7 R expression is increased in response to OGD in vitro or MCAO in vivo, Wang et al showed decreased expression of P2X 7 Rs in cultured oligodendrocyte precursor cells, the predominant oligodendrocyte-lineage stage in the cerebral hemispheres of the neonatal rat, after exposure to OGD for 2 h in vitro, and in a neonatal hypoxic-ischemic injury model in 3-day-old rats [14] . More recently, Zeng et al reported that OGD decreases P2X 7 R expression and modulates GSK-3β phosphorylation in radial glial clone L2.3 cells, and BzATP (a selective agonist of the P2X 7 R) induces L2.3 cell death in a dose-and time-dependent manner [27] .…”
Section: Receptors In Cerebral Ischemiamentioning
confidence: 81%
See 3 more Smart Citations
“…However, inconsistent with most reports that P2X 7 R expression is increased in response to OGD in vitro or MCAO in vivo, Wang et al showed decreased expression of P2X 7 Rs in cultured oligodendrocyte precursor cells, the predominant oligodendrocyte-lineage stage in the cerebral hemispheres of the neonatal rat, after exposure to OGD for 2 h in vitro, and in a neonatal hypoxic-ischemic injury model in 3-day-old rats [14] . More recently, Zeng et al reported that OGD decreases P2X 7 R expression and modulates GSK-3β phosphorylation in radial glial clone L2.3 cells, and BzATP (a selective agonist of the P2X 7 R) induces L2.3 cell death in a dose-and time-dependent manner [27] .…”
Section: Receptors In Cerebral Ischemiamentioning
confidence: 81%
“…Under normal conditions, P2X 7 Rs are widespread on the membranes of neurons, astrocytes, microglia, oligodendrocytes, and oligodendrocyte precursor cells, as well as Schwann cells [14,[25][26][27] , unlike the localization of P2X [1][2][3][4][5][6] receptor subtypes, which is mainly on the membranes of neurons [28] . They are especially abundant on microglia that are in a physiologically resting state, [20] , and play protective roles such as host defense and tissue repair [28] against neuronal damage [29] , suggesting that P2X 7 Rs are involved in immune functions and inflammatory responses [13] .…”
Section: Physiological Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these data, obtained in several models of disease, suggest that P2X7R contributes to damage exacerbation; however, it has also been reported that the expression of P2X7R was downregulated in OPC cultures and in ischaemic cerebral cortex, subcortical white matter and hippocampus in a paradigm of perinatal hypoxia-ischaemia, probably in an attempt to prevent the excessive receptor stimulation in the early stages of damage [99].…”
Section: Oligodendroglial Precursor Cells (Ng2-glia)mentioning
confidence: 97%